Educated Youth as Driving Force of Urbanization: The Role of Higher Education and the Employment Opportunities in Emerging Cities in Indonesia - Hasan, Hurriah (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
City growth is often associated as a symptom of urbanization, which is interpreted as a process of changing the proportion of the population living in urban areas. Urbanization occurs when population moves from rural to urban areas, which causes the growth rate of the urban population to be greater than the rural population. Urbanization can be interpreted as the process of a region becoming a city due to the strong influence of city center activities. This research aims to identify the causes of urbanization in emerging cities in Indonesia among educated people by using a qualitative approach to explore the reasons why educated people do not return to their hometowns after completing their education. There were seven informants who had just finished college, interviewed to get an idea of the future they hoped for. All informants expressed a desire to return to their hometown, but job opportunities were very limited due to their high level of education. The respondents stated that they would look for work in urban cities after graduating. Several respondents stated that they were willing to return to their hometowns if there was certainty that they could work in government offices. The findings of this research show that it is very important to encourage development in various sectors in rural areas that can absorb highly educated workers. In the case of educated young people, they are willing to return to their hometowns because there are sufficient job opportunities.